Stress-induced impairment reveals the stage and features of post-error adaptive adjustment - Hu, Na; Long, Quanshan; Zhang, Dawei; Wang, Xiaoxi; Deng, Min; Li, Qing; Yan, Minmin; Chen, Antao (Frontiers in Behavioral Neuroscience, 2022)
An increased reaction time often occurs after error responses (post-error slowing, PES). However, the role of top-down regulation in post-error processing remains debated. Impairing cognitive control function through acute stress would help to investigate the role and stage of top-down adaptive regulation in post-error processing. Here, we recruited 50 healthy male participants randomly exposed to either a stress condition (Trier Social Stress Task, TSST) or a control condition (control version of the TSST). A color-word Stroop task with different response stimulus intervals (RSI) was used to explore the effects of acute stress on different stages of post-error processing. The results showed that cortisol, heart rate, stress perception reports, and negative emotions were higher in the stress group (n = 24) than in the control group (n = 26), indicating successful stress induction. The accuracy of post-error response in the control group increased with the extension of RSI, and the reaction time decreased. However, the accuracy of 1200-ms RSI was close to that of 700-ms RSI in the stress group but significantly lower than that in the control group. The results suggested that acute stress caused the impairment of top-down adaptive regulation after error. Furthermore, our study manifested adaptive adjustment only in the late stages of post-error processing, indicating the phasic and adaptive features of post-error adjustment.